2017
DOI: 10.1111/nmo.13016
|View full text |Cite
|
Sign up to set email alerts
|

Methods of anorectal manometry vary widely in clinical practice: Results from an international survey

Abstract: There is significant discrepancy in methods for data acquisition, analysis, and interpretation of ARM. This is likely to impact clinical interpretation, transfer of data between institutions, and research collaboration. There is a need for expert international co-operation to standardize ARM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 71 publications
2
96
0
6
Order By: Relevance
“…Guidance with regard to data acquisition, methodology, analysis techniques, and reporting have been provided by various position statements and guidelines . However, as has recently been shown for anorectal manometry, it is widely presumed that there is marked variation between institutions and operators. Because much of what is observed remains subjective and (to a degree) open to subjective interpretation, reporting of a minimum dataset with technology and techniques of a minimum standard are imperative, and these should be regulation and not industry driven.…”
Section: Introductionsupporting
confidence: 72%
“…Guidance with regard to data acquisition, methodology, analysis techniques, and reporting have been provided by various position statements and guidelines . However, as has recently been shown for anorectal manometry, it is widely presumed that there is marked variation between institutions and operators. Because much of what is observed remains subjective and (to a degree) open to subjective interpretation, reporting of a minimum dataset with technology and techniques of a minimum standard are imperative, and these should be regulation and not industry driven.…”
Section: Introductionsupporting
confidence: 72%
“…The problem of uncertainty regarding normal range for ARM in studying anal sphincter integrity and sensory testing has been extensively discussed . It is therefore of importance to provide normal range for the still commonly used water‐perfused high‐resolution manometry catheter, utilizing the most updated comprehensive testing protocol available. In addition to the more commonly reported anal sphincter resting and squeeze pressures and rectal sensation thresholds, we also report a normal range for duration of sustained squeeze and cough pressure.…”
Section: Discussionmentioning
confidence: 99%
“…No published study to date has directly compared the different balloons used for testing and little emphasis has been placed on this variable . For ARM testing, although studies have reported normal reference values for solid‐state high‐resolution manometry systems, similar updated publications for the still commonly used water‐perfused high‐resolution systems are lacking . Historical testing protocols focused more on anal resting and squeeze pressures, and less on parameters such as anal pressure on cough, duration of anal squeeze and the push maneuver .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the association of FACL with symptoms of FI in the above studies, the definition of FACL was different between the centers and the methodology of measurement was poorly described, making it difficult to interpret the results and extrapolate them in comparison to our findings. A more precise description and standardization of measurement is needed to compare the results between different studies, in order to improve the diagnostic accuracy of HR‐ARM . Nevertheless, our results suggest that measurement of FACL does not improve manometric diagnostic utility.…”
Section: Discussionmentioning
confidence: 79%